The interaction of message content, media sequence, and product involvement: an examination of intended message content sequences across a two-channel strategic IMC effort - Martin, Ashley N. (Kansas State University, 2014)
Integrated marketing communications strategies are being utilized more and more by practitioners who wish to reach their audiences in different ways at different times. However, the omnipresence that results from these multi-channel campaigns presents a new challenge for marketers, as their message and channel sequences may or may not be experienced in the order intended. Past literature has shown that both message order and channel sequence do matter. However, existing literature has not examined intended message sequences where the first channel “teases” the more comprehensive information available in the second channel. Therefore, the aim of this study was to bridge some of the gaps in past research by exploring message content order effects and channel sequence effects across intentional sequences for both high- and low-involvement product categories through the lens of the Elaboration Likelihood Model. A 2 (message content order: tease-to-answer versus answer-to-tease) by 2 (medium sequence: print-to-online versus online-to-print) by 2 (product involvement: high- versus low-involvement) mixed factorial experimental design was conducted to explore how message content order, channel sequence, and product involvement level affected evaluations of brand and message, as well as perceived behavioral intent. The findings indicated that message content order had significant influence over brand and message evaluation, with the tease-to-answer order producing the highest evaluations of brand and message. The findings also indicated that the online-to-print sequence was only effective for increasing behavioral intent under high-involvement conditions. Implications for marketing practitioners and future research are discussed.
Keywords: Integrated marketing communications; Product involvement; Message sequence; Channel sequence; Elaboration likelihood model; Need for closure; Marketing (0338); Mass Communications (0708)